The dynamic impact of macroeconomic news on long-term inflation expectations - Michael Hachula; Dieter Nautz (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2017)
Well-anchored inflation expectations should not react to short-term oriented macroeconomic news. This paper analyzes the dynamic response of inflation expectations to macro news shocks in a structural VAR model. As identification of structural macro news shocks is controversial, we use a proxy SVAR model where, by construction, unobservable macro news shocks correlate with observable surprises from macroeconomic news announcements. Our results confirm that macro news shocks have no impact on U.S. long-term inflation expectations in the long run. In the short run, however, the degree of expectations de-anchoring is non-negligible.
Keywords: E31; E52; C32; 330; dynamics of inflation expectations; expectations anchoring; macroeconomic news; proxy SVAR